Analysis of the Impact of the Implementation of IT Service Management on the Operational Efficiency of PT Sinergis Utama Informasi Transformasi - Luntungan Stephen Pieters; Erick Dazki (INOVTEK Polbeng - Seri Informatika, 2024)
This research aims to assess the impact of the implementation of IT Service Management (ITSM) on operational efficiency at PT Sinergis Utama Informasi Transformasi. The company is facing challenges in optimizing IT services, which is impacting delays, increasing operational costs, and decreasing service quality. We chose ITSM as the approach to address this issue, focusing on more structured service management. The research utilized simple linear regression analysis with a sample of 40 employees directly involved in the implementation of ITSM. The results indicate that ITSM has a positive and significant impact on operational efficiency, with a regression coefficient of 0.693 and a significance level of 0.000. The F-test showed an F value of 37.282, confirming a significant relationship between the implementation of ITSM and operational efficiency. This finding confirms that the implementation of ITSM enhances IT service performance, optimizes resources, and boosts company productivity. We recommend expanding the application of ITSM to other operational areas and consistently monitoring ITSM metrics to ensure continuous improvement in services and operational performance.